A facile approach towards chemical modification of Ag nanowires by PEDOT as a transparent electrode for organic solar cells. Issue 2 (18th December 2017) - Zhou, Huanyu; Wang, Yilin; Zhang, Jingwen; Yu, Zoukangning; Li, Yaowen; Tan, Licheng; Chen, Yiwang
Abstract : A PEDOT:PSS:S-AgNWs transparent electrode has been prepared via in situ polymerization due to electrostatic interactions between PEDOT and the sulfonic groups in the PSS:S-AgNWs template. Abstract : Among the recent investigations on transparent electrode materials applied in photoelectric devices, poly(3, 4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) has been widely used because of its high transparency and low material cost. However, its relatively low conductivity, hygroscopicity, and acidity limit its further application. Herein, a novel PEDOT:PSS:S-AgNWs composite has been prepared via the in situ oxidative polymerization of EDOT using PSS and 4-mercaptobenzenesulfonic acid-modified silver nanowires (S-AgNWs), in which there are electrostatic interactions between PEDOT and sulfonic groups from PSS and S-AgNWs. When compared with commercial Clevios PH1000, a more crystalline and conductive PEDOT with quinoid conformation was developed by partially substituting PSS with the S-AgNWs; this resulted in the formation of PEDOT:PSS:S-AgNWs showing a lower sheet resistance (64 Ω sq −1 at ∼94.8% transmittance). Furthermore, due to reduced work function, hygroscopicity, and acidic properties of PEDOT:PSS:S-AgNWs derived from the in situ composite between S-AgNWs and PEDOT, as well as the reduction in the PSS content, PEDOT:PSS:S-AgNWs was used as a transparent electrode for the formation of organic solar cells (OSCs), displaying a power conversion efficiency of 10.2% and good storage stability.